Hospitalization for drug-related disorders in Italy: trends and comorbidity - Alessandra Burgio; Francesco Grippo; Marilena Pappagallo; Roberta Crialesi (Epidemiology, Biostatistics and Public Health)
Background: The drug abuse has several health, social and economic effects. Hospital discharge records(HDR) collected by the Ministry of Health represent a major source of epidemiological data. In this paper we used this source in order to assess drug abuse hospitalization patterns and trends in Italy by means of the study of comorbidity at discharge. Methods: Analysis are based on the National HDR Register and refers to data from 1999 to 2011 for the Ital-ian resident population. Two approaches have been followed: the main diagnosisand the comorbidity approach based on the analysis of all diagnoses reported on the HDR. As a measure of the association between drug-related disorders and specific conditions reported, an estimation of age-standardised relative risk (RR) has been used. Results: The number of hospitalizations for drug-related diagnosis declined from 10,968 cases in 1999 to 6,180 in 2011.Using the comorbidity approach we found that in the period 2009-2011 the number of HDR with a mention of drug use is 2.8 times higher than the number based only on the main diagnosis.The conditions more strongly associated to the group of drug users are mental disorders, alcohol abuseand infectious diseases such as HIV disease and viral hepatitis. Conclusions : These data can provide important information about the epidemiology of drug problems and the impact of drug policies.In addition the strong evidence of association of drug abuse and mental health provides a solid underpinning for planning more coordinated interventions of prevention and public health.